IMPLEMENTING MULTIMODAL PEDAGOGY FLIPPED CLASSROOM (MPFC) TO PROMOTE EFL STUDENTS’ SPEAKING ABILITY AND THEIR AUTONOMY - Faridah, Didih; Ratnawati; Thoyyibah, Luthfiyatun; Nurani, Desi; Pebriani Permana, Sherly; Yohana, Adila (University of Kuningan, 2025)
Multimodal Pedagogy Flipped Classrooms (MPFC) are well regarded for professional, pedagogical, and practical contributions to classroom practices in global context. Yet, Indonesian education setting has not provided significant attention, and the implementation of MPFC should be cultivated further for its benefit in language learning. Therefore, the present study investigates the impact of the MPFC to promote students' performance of speaking skill, measure the relationship of speaking ability and their level of autonomy, and exploring students' perception of MPFC implementation. The study conducted a mixed method which involved sixty students learning English as a foreign language from a private university in Indonesia and 6 selected students for interviews data collection. The quantitative research mediated MPFC for experimental class and product-based approach for control class while the qualitative research design using classroom observation and semi-structured interviews. The obtained data were analyzed using independent t-test and ANOVA for quantitative purpose, and thematic analysis to interview. The results show a profound difference in students' speaking from the pretest (M=77.00 SD=4.85) to the post-test (M=80.90 SD=3.12). Moreover, the relationship between their speaking skill and autonomy reveal betterment after MPFC implementation (t-value 0.003). Students perceive positively toward this pedagogical intervention including their experience, challenges, and their strategy to cope with challenges found. The implications and recommendations of the study are also discussed.